EVALUATING THE EFFECTIVENESS OF EPIDURAL ANESTHESIA AFTER CESAREAN SECTION AT NGHE AN PEDIATRICS AND OBSTETRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: The study was carried out with the aim of comparing the analgesic effect of localanesthesia with general anesthesia in cesarean section at Nghe An Obstetrics and Children'sHospital.Methods: Research 120 patients undergoing cesarean section with ASA I and II, aged 18 to 42years, who were divided into two groups: group A (n=60) decreased Post-operative pain withanaropine combined with fentanyl via local anesthetic and group B (n=60) postoperative analgesiawith intravenous paracetamol and intramuscular morphine. Evaluation of results by monitoringVAS pain scale, unwanted effects and complications in 24 hours after surgery.Results: Results did not differ between the two groups in terms of age, weight, ASA, and timeof surgery. The average VAS pain score in group A was lower than in group B at all time points offollow-up (p
Keywords: Pain relief, epidural anesthesia, postoperative pain relief.